Highly crystalline carbon nitride with small-sized sea urchin-like structure for efficient photocatalytic hydrogen production under visible-light irradiation. (December 2022) - Song, Jia; Liu, Xiaolei; Zhang, Caiyun; Cui, Zihao; Zhang, Qianqian; Qin, Xuesen; Wang, Zeyan; Zheng, Zhaoke; Liu, Yuanyuan; Cheng, Hefeng; Dai, Ying; Huang, Baibiao; et al.
Abstract: Molten-salt method has been deemed as a feasible strategy to increase the crystallinity of graphitic carbon nitride (abbreviated as CN), thereby improving its photocatalytic activity. However, highly crystalline CN prepared by molten-salt method using bulk carbon nitride (BCN) as the precursor still suffers from a small specific surface area, which is unfavorable to the separation of photogenerated carriers. Here, we report a facile approach to obtain highly crystalline CN with a large specific surface area using tubular carbon nitride (TCN) as raw material, and the final sample is named as tubular carbon nitride-molten salt (TCN-M). Compared with bulk carbon nitride-molten salt (BCN-M) sample, the obtained TCN-M sample not only retains the advantage of high crystallinity, but also exhibits a smaller-sized sea urchin-like structure owing to the CN precursor pretreatment process. The experiment results demonstrate that TCN-M displays an excellent hydrogen production activity of 4.9 mmol g −1 h −1 under visible-light, and its hydrogen production performance can be further enhanced to 14.7 mmol g −1 h −1 after adding 0.5 M K2 HPO4 . Thus, this work may supply valuable ideas to further optimize the photocatalytic activity of highly crystalline CN prepared by molten-salt method from the perspective of CN precursor pretreatment. Graphical Abstract: ga1 Highlights: A highly crystalline carbon nitride with small-sized sea urchin-like structure was successfully prepared. Large specific surface area and the presence of cyano groups greatly improve the photocatalytic H2 production activity. Optimizing the photocatalytic activity of highly crystalline CN from the perspective of CN precursor pretreatment. A typical H + -reduction cycle can be constructed by introducing K2 HPO4 into the reaction system.